Pemberhentian PPAT Yang Dinyatakan Pailit Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 2016 - Rahayu Kusuma Astuti (Fakultas Hukum Universitas Mataram, 2017)
This study aims to determine the responsibility and liability of PPAT declared bankrupt based on Government Regulation No. 24 of 2016 concerning Amendment of Government Regulation No. 37 of 1998 concerning on the Position of Land Titles Registrar and reappointment of PPAT which has been bankrupt. This research is normative law research by using the approach of legislation and method of concept approach where analyzed by using method of interpretation and invention of law. The result of this research is that the responsibility of PPAT which is declared bankrupt is to accept sanction of dismissal with respect to his position and the liability of PPAT which declared bankrupt to have to pay the debts arising from bankruptcy that the fulfillment comes from his wealth. PPAT which has completed bankruptcy process and obtained rehabilitation can not necessarily be reappointed as PPAT.